DIGESTIBILITY EVALUATION OF FISH MEAL, RICE BRAN, SOYA BEAN MEAL, POLLARD ON ONGOLE CROSS BREED CATTLE AND FRISIEN HOLSTEIN CROSS BREED - Muhammad Askari Zakariah; Ristianto Utomo; Subur Priyono Sasmitho Budhi (Journal of Livestock Science and Production, 2018)
The objective this study was to evaluate feed stuff such as fish meal, rice bran, soya bean meal, and wheat pollard on Ongola and Frisien Holsten breed. Each feed stuff was replicated in 3 replication. Variable were observed in vivo, in sacco, and in vitro digestibility. Collected data were analyzed by independent t-test sample. Result showed dry matter and organic matter in vitro digestibility of soya bean meal on Ongole crossbreed cattle has lower than Frisien Holstein crossbreed cattle (84.54±1.15 vs 90.17±1.34, 82.53±1.20 vs 89.05±0.76) respectively, and for another feedstud were used on this research not showed significant. Degradation theory of some feed stuff on Ongole crossbreed cattle has lower than Frisien Holstein crossbreed cattle. Coeficient of digestibility on ongole crossbreed cattle has lower than Frisien Holstein crossbreed cattle. Concluded that concentrate such as fish meal, soya bean meal, rice bran and pollard has digestibility on ongole crossbreed cattle lower than Frisien Holstein crossbreed.